Does GDP Moderates Capital Structure, Working Capital, and Financial Constraints Effecting Firm Performance? Study Case on Indonesia’s Manufacture Company - Cuandra, Fendy; Jones, Ivan (Politeknik Negeri Bengkalis, 2023)
In managing a company, reaching a high revenue is the most important goal. Indonesia’s Gross Domestic Product (GDP) experiences rise throughout 2017 by covid-19 outbreak in 2020. In the same time, Indonesia’s state income tax revenue also experiences the same condition which means, firms are having good performance from 2017 till by Covid-19 breakout in 2020. By analyzing firm’s cash flow source, we will find out the way of managing cash flow to reach a better return. Start-up capital usually comes from debt or shareholders, while in making sure operational cash usually comes from receivable turnover and future cash flow depends on financial constraints This Research aims to find out if firm performance is effected by cash flow management that is measured by Debt Equity Ratio (DER), receivable turnover, and financial constraints. Research was done on industry sectors of Indonesia which contributes more than 20% of Indonesia’s GDP since 2018.